Curtir, compartilhar, aprender e ensinar: possibilidades de uso do facebook como ambiente de ensino-aprendizagem no Instituto Federal do Rio Grande do Sul (IFRS) - Baratto, Mariângela Barichello (2018)
At a time when access to information is not restricted to school environments, new forms of teaching-learning emerge. The set of information, knowledge, economy and culture form the so-called networked society and, among other things, evidence new educational needs. In this context, we highlight the educational platforms that aim at the formation of networks for teaching and learning. From this, the present research developed during the Professional Master's Degree in Educational Technologies in Network of the Federal University of Santa Maria,,having as concentration area Educational Technologies in Network for Innovation and Democratization of Education and Line Research of Management of Educational Technologies in Network presents the social networking site Facebook as a new learning space and, from a networked thinking, to consider new ways of producing, creating, reading and sharing knowledge in this environment. The work evidence already explored known tools of Facebook as an interpersonal communication space, also identifying its potentialities still unexplored in the educational scope, in order to make it even more relevant, facilitating and constructive teaching-learning environment in the Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul (IFRS). The achievement of this reasearch was made from the union of methodological procedures, they are: bibliographic analysis allied to a case study and priority qualitative data collection, constructed from observations, questionnaires and interviews. Data will be analyze based on content analysis by categories. In the study, it will explore some key concepts that mainly involve: education, networks and technology, virtual teaching-learning environments, teacher-student relationship, education and communication through social networks, network interaction and collaboration. The results showed that Facebook can be seen and explored as a virtual environment of teaching and learning, allowing a greater dynamism, autonomy and interactivity to teaching and learning, being fundamental that teachers and students understand the ways of using that tool and their role as strategic agents in the process of teaching and learning. The research presents theoretical and practical products, being the master's dissertation - as a theoretical compiler of the study - and a Guide of Guidelines for use of Facebook as a teaching-learning environment in IFRS - as a practical product that gathered information and guidance on how teachers and IFRS students may use the social networking site for teaching-learning at the institution.